Periprosthetic Joint Infections Caused by Candida Species-A Single-Center Experience and Systematic Review of the Literature - Grzelecki, Dariusz; Grajek, Aleksandra; Dudek, Piotr; Olewnik, Łukasz; Zielinska, Nicol; Fulin, Petr; Czubak-Wrzosek, Maria; Tyrakowski, Marcin; Marczak, Dariusz; Kowalczewski, Jacek (Journal of fungi (Basel, Switzerland), 2022)
BACKGROUND: The aim of this study was to analyze the treatment results of fungal periprosthetic joint infections (PJI) caused by Candida species from a single orthopedic center and to compare them with reports from other institutions. METHODS: Eight patients operated on from January 2014 to December 2021 met the inclusion criteria and were analyzed in terms of clinical outcomes. A systematic review of the literature identified 153 patients with Candida PJIs extracted from 12 studies according to the PRISMA (Preferred Reporting Item for Systematic Reviews and Meta-Analyses) guidelines. RESULTS: The success rate of the treatment in the case series was 50%. The most frequent pathogens were Candida albicans (three cases; 37.5%) and Candida parapsilosis (three cases; 37.5%). In one patient (12.5%), bacterial co-infection was noted, and in five patients (62.5%) significant risk factors of PJI were confirmed. The overall success rate on the basis of data collected for systematic review was 65.5%. A sub-analysis of 127 patients revealed statistically significant differences (p = 0.02) with a higher success rate for the knees (77.6%) than for the hips (58%). In 10 studies the analysis of risk factors was performed and among 106 patients in 77 (72.6%) comorbidities predispose to fungal PJI were confirmed. Bacterial co-infection was noted in 84 patients (54.9%). In 93 patients (60.7%) Candida albicans was the culprit pathogen, and in 39 patients (25.5%) Candida parapsilosis was the culprit pathogen. Based on these two most frequent Candida species causing PJI, the success rate of the treatment was statistically different (p = 0.03), and was 60.3% and 83.3%, respectively. The two-stage strategy was more favorable for patients with Candida parapsilosis infections (94.4% success rate) than the one-stage protocol (50% success rate; p = 0.02); as well as in comparison to the two-stage treatment of Candida albicans (65% success rate; p = 0.04). CONCLUSIONS: The analysis of the literature showed no differences in the overall success rate between one- and two-stage surgical strategies for all Candida species, but differed significantly comparing the two most frequent strains and concerning PJI localization. The frequent presence of bacterial co-infections makes it necessary to consider the additional administration of antibiotics in the case of fungal PJI.
Keywords: Candida albicans; Candida parapsilosis; fungal pathogens; periprosthetic joint infections